Growth and mortality of the South African anchovy, Engraulis capensis (Gilchrist) - Pollock, D. E.(David Edward) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1970.